If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15x + -20 = -13x + 100 Reorder the terms: -20 + -15x = -13x + 100 Reorder the terms: -20 + -15x = 100 + -13x Solving -20 + -15x = 100 + -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. -20 + -15x + 13x = 100 + -13x + 13x Combine like terms: -15x + 13x = -2x -20 + -2x = 100 + -13x + 13x Combine like terms: -13x + 13x = 0 -20 + -2x = 100 + 0 -20 + -2x = 100 Add '20' to each side of the equation. -20 + 20 + -2x = 100 + 20 Combine like terms: -20 + 20 = 0 0 + -2x = 100 + 20 -2x = 100 + 20 Combine like terms: 100 + 20 = 120 -2x = 120 Divide each side by '-2'. x = -60 Simplifying x = -60
| 8x+15-5x-2= | | -3u+4= | | -2-2(N-3)-3N=21+7 | | 13x-(5+7x)= | | X/2-85=3x/11+270 | | -10=10y-60 | | X=-36-7/10x | | 3+x=31-5/9x | | 4s+8=4 | | 2T+3=5-2T+6 | | 15h-24=36 | | 49=12+x/7 | | -60=-5x+5(-x+10) | | 4y+16=24 | | 9k^2= | | 7(-3+x)=4(3-x) | | M+4=2M-3 | | 5t^2+45k=0 | | 3a^2-6a+8+6a^2-4+2a^2-a+12= | | 9m^2-88m+63=0 | | 5+4x=x-4 | | 117=2x+15 | | 2(x-4)=6(x+2) | | 3g+1=3 | | 117=2x+y | | 3/4(x-2)+3/5-1/5(x+1) | | -106=2x-6(x+11) | | 2x-2=900 | | 1=(117-x)/2 | | (x/8)-6=5 | | y/7-6=11 | | 16-q/11=9 |